The Effect of Differences in Temperature and Storage Time on Characteristics of Vannamei Shrimp (Litopenaeus vannamei) Intensive Pond - Fikri, Izzul (Journal of Aquaculture Development and Environment, 2023)
Indonesia has great potential in the development of the fisheries sub-sector consisting of capture fisheries and aquaculture. Shrimp is Indonesia's main export commodity in the fisheries sector. One type of shrimp, namely, vannamei shrimp. Vannamei shrimp have the characteristics of being able to live in the salinity range of 5-45 ppt with optimal salinity of 10-30 ppt; temperature range of 24° - 32°C with an optimal temperature of 28° - 30°C; The protein requirement is low, namely 32% with an FCR of 1.5 and the percentage of meat is 66 – 68%, higher than tiger prawns which is only 62%. The principle of freezing shrimp is one way to slow down the process of quality degradation, either by autolysis, bacteriology, and oxidation. This research is an experimental study that consists of the main parameters, namely the value of protein content, Total Volatile Base, and supporting parameters of organoleptic test values (color, aroma, texture) in vannamei shrimp with differences in temperature and shelf life. Consisting of independent variables, namely shelf life and temperature, dependent variables, namely protein, organoleptic, and TVB, as well as control variables of vannamei shrimp size 100 with an age of 2 months, and storage media. A completely Randomized Design (CRD) was used as the experimental design. Data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT). The results showed that the effect of shelf life and differences in freezing temperature of vaname shrimp, on protein and TVB levels of white vaname shrimp had met the quality requirements so that it was suitable for consumption and obtained the highest average value for each parameter of texture, color, and odor, namely 7 in the shrimp freezing treatment for 1 day at a temperature of -5°C.